Mister B. Gone - Barker, Clive 1952- (HarperCollins, 2007)
A medieval devil speaks directly to the reader, his tone murderous one moment, seductive the next, in a memoir allegedly penned in the year 1438. The demon has embedded himself in the very words of this tale of terror, turning the book itself into a dangerous object, laced with menace only too ready to break free and exert its power.